Confinement Alters the Structure and Function of Calmodulin. Issue 2 (9th December 2016) - Xu, Guohua; Cheng, Kai; Wu, Qiong; Liu, Maili; Li, Conggang
Abstract: Many cellular reactions involving proteins, including their biosynthesis, misfolding, and transport, occur in confined compartments. Despite its importance, a structural basis of understanding of how confined environments alter protein function is still lacking. Herein, we explore structure–function correlations of calmodulin (CaM), a multidomain protein involved in many calcium‐mediated signaling pathways, in reverse micelles. Confinement dramatically alters CaM structure and function. The protein forms an extended structure in bulk water, but becomes compacted in reverse micelles. In addition, confinement changes the function of CaM. Specifically, the protein binds the MLCK, AcN19, and somatostatin peptides in dilute buffer, but binds only the MLCK and AcN19 peptides in reverse micelles. In summary, we determined a new CaM structure in reverse micelles and demonstrate that confinement can modulate both protein structure and function. Abstract : Confinement matters : Calmodulin (CaM), a multi‐domain protein involved in many calcium‐mediated signaling pathways, mainly forms an extend structure in bulk water, but becomes compacted in reverse micelles, suggesting that confinement dramatically alters CaM structure.